Evaluating broad-scale habitat model against patchy benthic habitats: the case of EUSeaMap - Radicioli, Martina; Annunziatellis, Aldo; Agnesi, Sabrina; Giusti, Michela; Angiolillo, Michela; Tunesi, Leonardo (Frontiers in Marine Science, 2025)
Broad-scale habitat mapping plays an increasingly central role in ecosystem-based marine management. Among the available products, EUSeaMap provides a consistent, large-scale representation of benthic habitats across European seas. However, modeling habitats with irregular and discontinuous distributions, such as coralligenous reefs, remains a significant challenge. This study evaluates how EUSeaMap models these complex biogenic habitats, using ground-truth data collected under the Marine Strategy Framework Directive in Italian waters. The analysis involved the spatial correspondence between EUSeaMap-predicted habitats and ground-truth observations of the habitat-forming species that structure coralligenous reefs, applying a three-zone approach (core – modeled habitat, buffer – nearby area, and gap – area beyond the buffer) in order to determine the difference between model resolution and in-situ observations. The results show that EUSeaMap successfully detected 25% of the occurrences of coralligenous reefs. This percentage increased to 40% when considering the buffer zone, indicating that many observed occurrences were located near the zones where the model predicts habitat presence. Building on these findings, the study demonstrates how this broad-scale habitat model detects distributed habitats irregularly. In particular, it also highlights both the current capabilities of EUSeaMap and the areas for improvement, thus reinforcing its role as a reliable tool for marine habitat mapping and supporting its wider application to monitoring, conservation, and spatial planning across European marine initiatives.